Adjoint volume-of-fluid approaches for the hydrodynamic optimisation of ships. Issue 1 (2nd January 2018) - Kröger, Jörn; Kühl, Niklas; Rung, Thomas
ABSTRACT: The paper is concerned with simulation-based shape optimisation in marine engineering flows. Attention is devoted to the derivation of an adjoint complement to two-phase flow finite-volume procedures. The strategy refers to an extension of a hybrid continuous/discrete adjoint method for volume-of-fluid (VoF) approaches. The study outlines means to formulate a discrete adjoint VoF scheme from the terms that originate from variations of the fluid properties. The adjoint solution is verified against results of a direct differentiation technique. The application is devoted to the drag optimisation of the Kriso container ship. A kernel-based self-parametrisation approach of the design surface is combined with mesh-morphing techniques to drive the 150, 000 shape parameters of the vessel without the need to revisit or differentiate the CAD environment during the optimisation. The optimisation process obeys to practical constraints. The optimised vessel displays more than 5% reduction of total drag while maintaining main dimensions and displacement.